(untitled) (One Health & Risk Management, 2023)
Introduction. Wilson’s disease represents one of the genetic diseases that has lifelong treatment, which significantly improved the quality of life for patients and reduced the disabling complications associated with the lack of an early diagnosis. Material and methods. A structured search was performed in PubMed and HINARI, using English search terms: "Wilson’s disease", "acute liver failure", "cirrhosis", "acute Wilsonian hepatitis", "hepatic manifestation", "chronic liver disease", "asymptomatic Wilson’s disease", and "active chronic hepatitis". Results. Wilson’s disease can occur at any age and can mimic the presence of other chronic liver diseases. The hepatic expression is highly variable, ranging from asymptomatic presentation to severe liver diseases, such as decompensated cirrhosis and acute liver failure. Any patient with transaminitis and abnormal parameters of cooper metabolism should be comprehensively and carefully evaluated to identify Wilson’s disease early and to prevent misdiagnosis or unnecessary therapies. Confirmation of the diagnosis should not exclude the co-existence of other liver diseases. Conclusions. The use of validated and adapted scores for Wilson’s disease may facilitate diagnosis, but they cannot be used in acute liver failure. Considering that WD presents itself with great phenotypic diversity and can evolve under the mask of other pathologies, it is necessary to carry out a careful differential diagnosis.